2012
DOI: 10.1002/adsc.201200179
|View full text |Cite
|
Sign up to set email alerts
|

Palladium on Carbon‐Catalyzed Cross‐Coupling using Triarylbismuths

Abstract: Simple and efficient protocols for the 10% palladium on carbon (Pd/C)-catalyzed crosscoupling reactions between triarylbismuths and aryl halides have been developed. A variety of iodoand bromobenzenes possessing an electron-withdrawing group on the aromatic nucleus were smoothly cross-coupled in the presence of 10% Pd/C, sodium phosphate dodecahydrate (Na 3 PO 4 ·12 H 2 O) and 1,4-diazabicycloA C H T U N G T R E N N U N G [2.2.2]octane (DABCO) in heated N-methyl-2-pyrrolidone (NMP) as the solvent. For the aryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…General Procedure for the Synthesis of Starting Materials. All amides used in this study have been previously reported and prepared by reported methods (Zhou et al, 2019;Liu et al, 2018;Monguchi et al, 2012;Lipshutz et al, 2008). Starting materials were synthesized according to general methods reported in the literature (Al-Huniti et al, 2018;Ackermann et al, 2011;Patel et al, 2012;Sun et al, 2016;Wang et al, 2017;Zhang et al, 2017).…”
Section: Experimental Procedures and Characterization Datamentioning
confidence: 99%
“…General Procedure for the Synthesis of Starting Materials. All amides used in this study have been previously reported and prepared by reported methods (Zhou et al, 2019;Liu et al, 2018;Monguchi et al, 2012;Lipshutz et al, 2008). Starting materials were synthesized according to general methods reported in the literature (Al-Huniti et al, 2018;Ackermann et al, 2011;Patel et al, 2012;Sun et al, 2016;Wang et al, 2017;Zhang et al, 2017).…”
Section: Experimental Procedures and Characterization Datamentioning
confidence: 99%
“…However, the reaction conditions of 5 mol% Pd/C (10 wt%), 20 mol% 2,2′‐biquinoline, 6 equivalents caesium fluoride, NMP and 140 °C are much better for the arylation of iodobenzenes. Furthermore, they also found a ligand‐free Pd/C‐catalyzed cross‐coupling reaction between aryl iodides and triarylbismuths in the presence of tetra‐ n ‐butylammonium fluoride trihydrate (TBAF⋅3 H 2 O) in NMP at 140 °C for 24 h. They indicated that palladium metal leached from the Pd/C catalyst into the reaction media in this case . Apart from triarylbismuths, the reaction of sodium tetraphenylborate with aryl bromides under focused microwave irradiation in water via Pd/C‐catalyzed C–C cross‐coupling was reported by Bai's group [Eq.…”
Section: Applications Of Pd/cmentioning
confidence: 96%
“…Shortly after these reports, Rao published similar protocols to cross-couple triarylbismuthines with bromopyridines and quinolines (Scheme 39 B). 239 Other catalytic systems have been used to promote cross-coupling reactions between organobismuth reagents and various electrophiles such as a reusable polystyreneresin-supported palladium catalyst, 240 palladium-on-carbon, 241 chloro-bridged arylpalladium complexes, 242 palladium(II) chalcogenolate complexes, 243 an MCM-41-immobilized palladium(II)-Schiff base complex [MCM-41-2N-Pd(OAc) 2 ] 244 and PEPPSI. 245 Resin-bound bromotriarylbis-muthine reagents have also been developed to perform solid-phase cross-coupling reactions with arylboronic acids.…”
Section: Cross-coupling With Aryl and Heteroaryl Halides And Pseudo Hmentioning
confidence: 99%